2008
DOI: 10.1152/jn.00659.2007
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide-Induced Potentiation in the Hippocampus Requires Activation of Ryanodine Receptor Type 3 and ERK

Abstract: Huddleston AT, Tang W, Takeshima H, Hamilton SL, Klann E. Superoxide-induced potentiation in the hippocampus requires activation of tyanodine receptor type 3 and ERK. J Neurophysiol 99: 1565-1571, 2008. First published January 16, 2008 doi:10.1152/jn.00659.2007. Reactive oxygen species (ROS) are required for the induction of longterm potentiation (LTP) and behave as signaling molecules via redox modifications of target proteins. In particular, superoxide is necessary for induction of LTP, and application of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…Blockade of RyRs restored basal [Ca 2ϩ ] i levels in IH cells to levels seen in control cells, implying that constitutive activation of RyRs mediates the elevated basal [Ca 2ϩ ] i levels in IH cells. We further demonstrate that IH leads to NOX/ROSdependent S-glutathionylation of RyR2, which is known to constitutively activate RyRs (Murayama et al, 1999;Zissimopoulos and Lai, 2006;Bull et al, 2008;Huddleston et al, 2008;Belevych et al, 2009). These observations taken together demonstrate that NOX/ROS signaling activates RyRs by transcriptional upregulation as well as by posttranslational modifications involving S-glutathionylation in IH-treated neonatal chromaffin cells resulting in constitutive activation of RyRs.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Blockade of RyRs restored basal [Ca 2ϩ ] i levels in IH cells to levels seen in control cells, implying that constitutive activation of RyRs mediates the elevated basal [Ca 2ϩ ] i levels in IH cells. We further demonstrate that IH leads to NOX/ROSdependent S-glutathionylation of RyR2, which is known to constitutively activate RyRs (Murayama et al, 1999;Zissimopoulos and Lai, 2006;Bull et al, 2008;Huddleston et al, 2008;Belevych et al, 2009). These observations taken together demonstrate that NOX/ROS signaling activates RyRs by transcriptional upregulation as well as by posttranslational modifications involving S-glutathionylation in IH-treated neonatal chromaffin cells resulting in constitutive activation of RyRs.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have shown that posttranslational redox modulation involving S-glutathionylation of cysteine residues activate RyRs under basal conditions (Murayama et al, 1999;Bull et al, 2008;Huddleston et al, 2008;Terentyev et al, 2008). To examine whether IH induces similar posttranslational modification of RyRs, adrenal chromaffin cell lystes were probed with anti-glutathionylated antibody and analyzed by immunoblot assay.…”
Section: Evidence For Ih-induced Redox Modulation Of Ryrs Via S-glutamentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria are also deeply involved in calcium homeostasis because they promote ER depletion by calcium buffering. Importantly, mitochondria calcium uptake stimulates ROS production, which plays a role in modulating ER and cytosolic calcium concentration (26) by affecting the activity of pivotal calcium signaling proteins via S-glutathionylation (20). We found that expression hCaSR-wt, hCaSR-R990G, and hCaSR-N124K not only reduced intracellular calcium level (13) but is also accompanied by a significant decrease of AQP2 S-glutathionylation secondary to a decrease of ROS content, which is associated to a relevant decrease of NADPH oxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Incubation of hippocampal slices with exogenous superoxide dismutase (SOD) attenuates LTP [47]. ROS can induce LTP by modulating the activity of a number of protein kinases such as PKA, PKC, CaMKII and ERK [48][49][50]. In addition, ROS can also induce LTP through suppression of the activity of a number of protein phosphatases, such as protein tyrosine phosphatase, protein phosphatase 2A and calcineurin [48].…”
Section: Rosmentioning
confidence: 99%